Peritoneal Dialysis in Children: Infectious and Mechanical Complications: Experience of a Tertiary Hospital in Elazig, Turkey - Bakal, U.; Sarac, M.; Tartar, T.; Aydin, M.; Kara, A.; Gurgoze, M. K.; Kazez, A. (Wolters Kluwer Medknow Publications, 2022)
Background: Peritoneal dialysis (PD) is frequently used in pediatric patients with renal failure. Aim: In the present study, we evaluated the indications and complications of PD and patients' outcomes in pediatric patients. Patients and Methods: Medical records of patients who underwent PD between 2012 and 2019 were analyzed retrospectively. The patients were divided into two groups as acute PD (APD) (Group 1) and chronic PD (CPD) (Group 2). If the patient was diagnosed with acute kidney injury (AKI), an APD catheter was inserted, while a CPD catheter was inserted for patients with stage 5 chronic renal failure or those in which AKI persisted for more than 6 weeks. Results: Group 1 and Group 2 consisted of 62 and 64 patients, respectively. The most common indications for PD were AKI (64.5%) in Group 1, and obstructive uropathy and reflux nephropathy (45.3%) in Group 2. The overall complication rate was 30%. These were leakage at the catheter insertion site (11.2%), catheter occlusion (4.8%), and peritonitis (4.8%) in Group 1; and peritonitis (14.1%), catheter occlusion (6.2%), and inguinal hernia (4.6%) in Group 2. The mortality rate was 72.5% and 23.4% in Group 1 and Group 2, respectively. The most common causes of mortality were multisystem organ failure (40%) and sepsis (33.5%) in both groups. A total of 83 patients (32 in Group 1 and 51 in Group 2) had omentectomy. Catheter revision and/or removal were performed in 11.9% of all patients. Omentectomy had no effect on the prevention of catheter occlusion (p > 0.05). Conclusion: The mortality rate is lower in CPD patients than in APD patients. Although PD in pediatric patients is associated with potential complications, its actual rate is relatively low. The primary catheter dysfunction rate is low, and omentectomy has no significant effect on preventing catheter occlusion.
Keywords: Children; complications; peritoneal dialysis; renal failure